Cardiovascular effects of intravenous morphine in anesthetized horse - Hoeberg, Emma; Haga, Henning Andreas; Lervik, Andreas (Frontiers in Veterinary Science, 2022)
Objectives: To investigate if morphine causes a change in mean arterial blood pressure (MAP) heart rate (HR) and oxygen extraction rate (OE) in healthy horses anesthetized with isoflurane and a dexmedetomidine infusion. Material and methods: The study design was prospective clinical, randomized, blinded two groups including 33 horses. All horses were sedated with romifidine IV, and anesthesia was induced with midazolam IV and ketamine IV and maintained with isoflurane in oxygen and medical air and a dexmedetomidine infusion. As a baseline venous and arterial blood, heart rate (HR) and mean arterial pressure (MAP) were sampled. Thereafter either morphine 0.1 mg kg-1 IV or an equivalent volume of NaCl 0.9% IV was administered. Heart rate and MAP were then further sampled for five minutes before venous and arterial blood was again sampled. Oxygen extraction (OE) was calculated based upon arterial and venous blood gas analysis. To evaluate the change in minimum MAP, mean HR and OE the differences between baseline and observation period values were, further termed delta MAP, delta HR and delta OE. Individual delta MAPs were normalized to the minimum baseline value and is reported as a percentage. Alpha was set to 0.05. Confidence intervals 95 % (CI) were calculated for delta MAP, delta HR and delta OE within groups, and for the difference between groups. Results: The 95 % CIs for delta MAP (%), delta HR (min-1) and delta OE (mL/dL) in the morphine group were -20.5 - -9.0, 0.6 - 3.1 and -0.1 - 0.6 and in the placebo group were -17.4 - -10.1, 0.2 - 2.0 and -0.2 - 0.3 respectively. The 95 % CI for the differences in delta MAP (%), delta HR (min-1) and delta OE (mL/dL) were -5.5 - 7.6, -2.3 - 0.7 and -0.7 - 0.2, respectively. The minimum MAP of one horse in the morphine group decreased around 50 % between baseline and observation period with almost unchanged OE and HR. Conclusion and clinical relevance: The effects of morphine 0.1 mg kg-1 IV on HR, MAP, and OE in healthy horses anesthetized with isoflurane and a CRI of dexmedetomidine are minimal.